Schroth Method Exercises for Treating Idiopathic Adolescent Scoliosis; A Narrative Review - Javid Mostamand (مجله پژوهش در علوم توانبخشی, 2019)
- Introduction: Scoliosis is a 3-dimensional spinal deformity. In recent years, more attention has been paid to scoliosis specific exercises. Among different exercise methods for treating scoliosis, the Schroth’s method is the most recognized and widely used. This study aimed to determine the effect of Schroth’s scoliosis specific exercises on different outcomes and quality of life in patients with idiopathic scoliosis.